2023
DOI: 10.3390/cancers15061772
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Supramarginal Resection versus Gross Total Resection in Glioblastoma: Can We Enhance Progression-Free Survival Time and Preserve Postoperative Safety?

Abstract: To date, gross total resection (GTR) of the contrast-enhancing area of glioblastoma (GB) is the benchmark treatment regarding surgical therapy. However, GB infiltrates beyond those margins, and most tumors recur in close proximity to the initial resection margin. It is unclear whether a supramarginal resection (SMR) enhances progression-free survival (PFS) time without increasing the incidence of postoperative surgical complications. The aim of the present meta-analysis was to investigate SMR with regard to PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Considering a meta-analysis by De Witt Hamer et 31 , the risk for late post-operative neurological de cit ranges from 3.4-8.4% of treated patients, while neurological de cits at discharge can reach nearly 30% of patients according to different series 28,32,33 . Such risks may increase in case of supramarginal resection 34 and it is under debate if such risk worth the potential bene ts 30,[35][36][37] : in a work by Aabedi et al 16 neurological integrity was found to be a key factor for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Considering a meta-analysis by De Witt Hamer et 31 , the risk for late post-operative neurological de cit ranges from 3.4-8.4% of treated patients, while neurological de cits at discharge can reach nearly 30% of patients according to different series 28,32,33 . Such risks may increase in case of supramarginal resection 34 and it is under debate if such risk worth the potential bene ts 30,[35][36][37] : in a work by Aabedi et al 16 neurological integrity was found to be a key factor for survival.…”
Section: Discussionmentioning
confidence: 99%
“… 56 , 57 Depending on the physiology of the tumour and the location, a range of studies have shown that SMR significantly improves PFS and OS of patients, compared to those that underwent GTR or partial resection surgery. 58 , 59 Other novel surgical procedures that improves GTR and prevents surgery‐associated complications involve using intraoperative imagining such as MRI or ultrasound for real‐time visualisation of the tumour region, fluorophores such as sodium fluorescein (SF) and 5‐aminolevulinic acid (5‐ALA), dyes that bind to proteins in the blood at the tumour site (SF fluorophore) or metabolised by cancer cells (5‐ALA fluorophore), which can be detected under ultraviolent light and the use of motor evoked action potentials in real‐time to help monitor vital regions of the brain that are involved in motor functions. These innovative procedures have shown significant improvements in GTR and survival rates in adults as compared to surgery alone.…”
Section: Current Management Of Paediatric‐type Diffuse High‐grade Ast...mentioning
confidence: 99%
“…Meta-analyses and systematic reviews examining the survival benefit of supratotal or supramaximal resection in GBM have largely shown that patients who undergo supratotal or supramaximal resection have longer progression-free survival (PFS) and OS compared to those who undergo GTR. Moreover, these studies have demonstrated that the complication rate associated with supratotal resection is not significantly higher than that associated with GTR ( Table 1 ) [ 12 17 31 32 ].…”
Section: Association Between Extent Of Resection and Survival In Gbm ...mentioning
confidence: 99%
“…Since Yordanova et al [ 9 ] described “supratotal” resection, similar concepts have also been referred to as “supracomplete” [ 10 ], “supramaximal” [ 11 12 13 14 ], and “supramarginal” [ 15 16 17 18 ] resection. On the other hand, the term “supratotal” has also been used with a slightly different meaning.…”
Section: Introductionmentioning
confidence: 99%